2020
DOI: 10.1159/000510140
|View full text |Cite
|
Sign up to set email alerts
|

AGE-Induced Suppression of EZH2 Mediates Injury of Podocytes by Reducing H3K27me3

Abstract: Background: Chronic hyperglycemia, a pivotal feature of diabetes mellitus (DM), initiates the formation of advanced glycation end products (AGEs) and the dysregulation of epigenetic mechanisms, which may cause injury to renal podocytes, a central feature of diabetic kidney disease (DKD). Previous data of our group showed that AGEs significantly reduce the expression of NIPP1 (nuclear inhibitor of protein phosphatase 1) in podocytes in vitro as well as in human and murine DKD. NIPP1 was shown by others to inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 46 publications
1
18
0
Order By: Relevance
“…Recent studies have suggested that renal aging may be one of the reasons for the tendency of elderly patients to suffer podocyte injury. 20,21 Further studies are required to determine whether kidney aging is associated with podocyte injury in Class II LN. Thrombocytopenia in SLE is typically caused by autoantibodies against platelet membrane and hyper-reactivity of B cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested that renal aging may be one of the reasons for the tendency of elderly patients to suffer podocyte injury. 20,21 Further studies are required to determine whether kidney aging is associated with podocyte injury in Class II LN. Thrombocytopenia in SLE is typically caused by autoantibodies against platelet membrane and hyper-reactivity of B cells.…”
Section: Discussionmentioning
confidence: 99%
“…Although alterations in H3K27 methylation have been reported in diabetic nephropathy, 67,68 they are scarce in the diabetic retina. In 2021, Duraisamy et al found that the levels of the H3K27 histone methyltransferase Ezh2 were increased at the MMP-9 promoter in diabetes, resulting in transcriptional activation of MMP-9.…”
Section: The Role Of Chloride Ion Channels and H3k27me3 In The Retina In The Early Stage Of T1dmmentioning
confidence: 99%
“…RAGE induces the conversion of VSMCs to osteoblasts through activation of signalling pathways such as ERK ( 163 ), NF-κB ( 164 ) and Wnt ( 160 ); thus, participating in VC. AGEs decrease EZH2 expression in podocytes and, consequently, reduces H3K27me3, causing an upregulated expression of pathological factors and contributing to podocyte injury in diabetic kidney disease ( 165 ). EZH2 is required in Wilm’s tumour 1 (WT1)-mediated β-catenin inactivation via repression of secreted frizzled-related protein 1 (SFRP-1), which is a Wnt antagonist, and EZH2-mediated silencing of SFRP-1 is due to increased H3K27me3 at its promoter area(s) ( 166 ).…”
Section: Hkmts Catalyze Lysine Substrates To Participate In the Mecha...mentioning
confidence: 99%